Transcriptional analysis of pmeA gene encoding a pectin methylesterase in Xanthomonas campestris pv. campestris - Hsiao, Yi-Min; Liu, Yu-Fan; Huang, Yi-Ling; Lee, Pei-Yu (Research in microbiology, 2011)
Exopolysaccharides and several extracellular enzymes of Xanthomonas campestris pv. campestris (Xcc), the causative agent of black rot in crucifers, are virulence determinants. It is known that Clp (cAMP receptor protein-like protein) and RpfF (an enoyl-CoA hydratase homologue required for the synthesis of the diffusible signal factor, DSF) regulate production of these factors. In this study, plate assay revealed that Xcc possesses pectin methylesterase activity and that its expression is controlled by Clp and RpfF. Mutational analysis has demonstrated that pmeA encodes a pectin methylesterase. Using the 5′ RACE method, the pmeA transcription initiation site was mapped. Transcriptional fusion assays showed that pmeA transcription is positively regulated by Clp and RpfF, subject to catabolite repression which is independent of Clp or RpfF, and repressed under conditions of high osmolarity or oxygen limitation. This study not only extends previous work on Clp and RpfF regulation by showing that they both influence the expression of pmeA in Xcc, but also, for the first time, characterizes pectin methylesterase gene expression in Xanthomonas.